Significance of 195 bp-enhancer of PdCYP51B in the acquisition of Penicillium digitatum DMI resistance and increase of fungal virulence - De-Ramón-Carbonell, Marta; Sánchez-Torres, Paloma (Elsevier, 2020)
Two sterol 14α-demethylase genes from Penicillium digitatum, PdCYP51A and PdCYP51B, were evaluated and revealed that 95% of Imazalil (IMZ)-resistant isolates carried a 195-bp insertion in the PdCYP51B promoter. We functionally characterized both sterol 14α-demethylases by overexpression. Molecular analysis of overexpression mutants showed that the introduction of PdCYP51B insertion is more stable than the five-tandem repeat PdCYP51A sequence previously described that confers DMI fungicide resistance. The both enhancers can coexist in P. digitatum isolates that initially contained the 195-bp PdCYP51B insertion but the introduction of 195-bp PdCYP51B enhancer promoted the loss of the five-tandem repeat of PdCYP51A. The incorporation of 195-bp PdCYP51B resulted in an increase of DMI fungicide resistance in mutants from already resistant isolates and confers resistance to DMIs in mutants from sensitive isolates. Transcription evaluation of the both genes showed noticeable induction in all overexpression mutants, except for those coming from the five-tandem repeat PdCYP51A sequence, whereas PdCYP51A expression dropped dramatically. Only PdCYP51B exhibited up-regulation during citrus infection compared to axenic growth, and the role of PdCYP51B in fungal virulence was further reinforced since strains with low virulence showed increased infectivity in overexpression mutants. This study suggested the predominant role of the PdCYP51B enhancer in the acquisition of DMI resistance and fungal virulence, by replacing homologues genes with same putative function.